Mengenal Urgensi Ijtihad - Nuraeni, Heni Ani; Supriatna, Muhammad Wildan; Ananda, Mimin; Rahman, Zahid Alfathu (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of his study was to determine the role and urgency of ijtihad as a method of extracting and discovering Islamic law from its main sources, the Qur'an and Sunnah. This method cannot be separated from the historical background, where times continue to change and develop, and new problems arise that are not regulated in legal texts. The results obtained using the Ijtihad method show that Islamic law is increasingly resilient with changes and developments over time and is evolving as an effective solution to various problems.